Magnetometry and ground penetrating radar in application to mapping of polygonal wedge ice of yedoma complex - L. V. Tsibizov; E. I. Esin; A. V. Grigorevskaya; K. A. Sosnovtsev; Л. В. Цибизов; Е. И. Есин; А. В. Григоревская; К. А. Сосновцев (Arctic and Antarctic Research, 2018)
Paper is dedicated to geophysical mapping of polygonal wedge ice. Magnetometric and ground penetrating radar surveys were implemented on a small area of Yedoma ice complex on Kurungnakh island in Lena river delta. Such deposits are widely spread on a huge areas of Siberia and Alaska. The study was conducted near the thermoerosional gully, which propagates along the most thick ice wedges. Polygonal pattern is observable on high-resolution aerial imagery and digital elevation model - this data was used during the interpreting of obtained results. Study area (40×50 m) was covered with highresolution magnetic survey at the elevation of 2 m with 2×2 m step and with ground penetrating radar survey along profiles with 1 m distance between the profiles. Map of total magnetic field anomalies allow to determine the ice wedges of Yedoma ice complex distinctly. Difference between maximum positive (polygons centers) and negative (ice wedges) anomalies reaches 6 nT (error of the survey is 0,3 nT). Beyond that smaller ice wedges which penetrate the ice wedges of Yedoma complex are also observable in magnetic field. Basing on ground penetrating radar data an amplitude slice of at 3,5 m depth was built. Yedoma ice wedges are observable at depth of 3–4 m. Ground penetrating radar data is quite noisy due to surface inhomogeneity (puddles, knolls, etc.). Results of the surveys were compared in the light of practical application of the methods for above mentioned goal. Magnetometric method appears as more efficient than ground penetrating radar survey: it does not require a contact with the surface and more rapid, it is more sensitive as the case stands. Ground penetrating radar method may have advantages in the case of natural (magnetic storm, high-magnetized overlaying deposits) and anthropogenic (metal constructions — pipelines, ETL) noise. На примере небольшого участка многолетнемерзлых отложений на острове Курунгнах в дельте р. Лены проведено сравнение эффективности методов магнитометрии и георадиолокации для картирования ...